Systemic action research: Changing system dynamics to support sustaina ble change - Burns, Danny (Action Research)
This article explores the characteristics of systemic action research. It looks at the conceptual underpinnings of systemic action research and explores some of the ways in which it differs from (builds on) oth er forms of action research. It then explores some of the issues and d ilemmas faced by systemic action researchers.